2017
DOI: 10.2166/wp.2017.131
|View full text |Cite
|
Sign up to set email alerts
|

Delphi technique as a consultation method in regulatory impact assessment (RIA) – the Portuguese water sector

Abstract: This paper explores use of the Delphi technique on regulatory impact assessment (RIA) in order to select criteria as well as to analyze the non-neutrality of stakeholders in the Portuguese case study. Although the decision-making process has been supporting a different prescriptive approach, there is no neutral decision, which can reflect on the (in)efficiency of the government's action. To cope with imperfect knowledge, we have built the link between the objectives from Law no. 194/2009, which determines the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…The Delphi Method is a research technique used to facilitate consensus within an expert group regarding underlying relationships among causal drivers (Linstone & Turoff, 1975). It has been used as a policy sector analysis approach for a wide array of sectors including water (Mayor et al, 2016;de Carvalho et al, 2017). The consensus is pursued through a multi-round survey whereby, in each subsequent round, panelists are presented with the aggregate group responses from the previous round to allow reconsideration of choices in light of the other participant responses and provide opportunities for experts to clarify their reasoning for either staying with or changing their response.…”
Section: Methodsmentioning
confidence: 99%
“…The Delphi Method is a research technique used to facilitate consensus within an expert group regarding underlying relationships among causal drivers (Linstone & Turoff, 1975). It has been used as a policy sector analysis approach for a wide array of sectors including water (Mayor et al, 2016;de Carvalho et al, 2017). The consensus is pursued through a multi-round survey whereby, in each subsequent round, panelists are presented with the aggregate group responses from the previous round to allow reconsideration of choices in light of the other participant responses and provide opportunities for experts to clarify their reasoning for either staying with or changing their response.…”
Section: Methodsmentioning
confidence: 99%
“…There is no uniformity in the academic and policy literature regarding both “regulatory governance” and “regulatory impact assessment.” In this paper, the authors refer to regulatory governance as the “process under which state and non‐state actors interact to design and implement policies related to utility regulation (the policy) under a certain regulatory regime (formal and informal rules)” (Carvalho, Marques, & Netto, ). Moreover, the authors define RIA as a “policy tool that systematically exams the potential impact arising from government action (Carvalho, Poleto, & Seixas, ) and should create a stimulus to improve the governance.” Both concepts could be connected in such a way that RIA may contribute equally to the results and the procedure of the regulatory function (Dunlop & Radaelli, ; Kirkpatrick & Parker, ).…”
Section: Regulatory Governance and Ria: In Briefmentioning
confidence: 99%
“…Empirical analyses conducted by the Organisation for Economic Co‐operation and Development through systematic surveys regarding the use of RIA have shown that this policy tool has enhanced governance and the quality of regulation (Organisation for Economic Co‐operation and Development, , ). Some researchers have highlighted that in developing countries, RIA has increased both integrity and trust in the policy‐making process, improving regulatory outcomes by promoting informed decision making and regulatory functions (Adelle, Macrae, Marusic, & Naru, ; Berg, ; Carvalho et al, ). Fukuyama () tried to conceptualize this notion as “the beginning of an effort to better measure governance” (p. 347), which has shown progress in addressing the ensuing challenges such as why and how to measure governance although such issues require specific knowledge.…”
Section: Regulatory Governance and Ria: In Briefmentioning
confidence: 99%
“…The Delphi technique is considered an excellent tool for obtaining consensus from a group of experts in a wide range of fields, such as applied psychology and psychotheraphy [60], the impact assessment of public policies [61], or strategy implementation for sustainable development [62], among others.…”
Section: Techniquesmentioning
confidence: 99%